Fatores associados ao nascimento pré-termo: estudo da coorte de nascimento de São Luís - MA - MELO, Angela Gabriela de Araújo Costa (2012)
The preterm birth is currently a major public health problem by contributing a portion of the high infant and child mortality. Its rate has grown considerably in some capitals. Epidemiological studies have shown several factors associated with its occurrence, despite being considered a complex and poorly understood etiology. The aim of this study was to identify factors associated with preterm birth in the city of São Luís-MA in 2010. We conducted a cross-sectional study that used the database of the research population cohort BRISA - "Etiology of Preterm Birth and consequences of perinatal factors on children's health." The sample was composed of hospital births in 10 public and private hospitals of São Luís in the period from January 1 to December 31 in 2010, a total of 5050 births, which were randomly selected from each maternity study, with subsequent exclusion of multiple births and stillbirths. Mothers answered a standardized questionnaire, the independent variables that were investigated were grouped into blocks, were candidates for the final regression model showed that the value of P <0.20, but remained only those with less than 0.10 for significance obtain better control of confounding. We performed the chi-square test and multivariate logistic regression to assess the association between the independent variables and preterm birth. In 2010, the prevalence of preterm birth was 11.82%. It was shown high rate of teenage pregnancy (18.66%) and cesarean rate above the recommended WHO (46.95%). Increased risk for preterm birth was observed among mothers aged under 18 years (OR=1.37) among those who lived without a partner (OR=1.52), which had income below one minimum wage (OR=1.21), which were primiparous (OR=1.22), who did not attend any antenatal consultation (OR=2.40) and among those who smoked during pregnancy (OR=1.77). We conclude that the rate of preterm birth is high and the cesarean and teenage pregnancy. Socioeconomic factors and reproductive is strongly associated with increased rate of preterm birth in São Luís.